lNCREASING VIOLENCE IN SPORT: A THREAT TO SOCIAL HEALTH - Ofili , Perpetua; ofili, Diana (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Research studies have shown that sport holds prominent place in our society as it serves as an important agency for character development. Over the years, sport provides viable ground for nursing and breeding deviant behaviour like violence. Sport in the recent time is used as a means to influence diplomatic, social and political relations. Many tribes and nations use sport arena as viable ground to exercise political supremacy and power tussle over one another. The material rewards associated with winning in the contemporary sports are so great that the athletes and coaches now imbibe the idea of "win at all cost" to obtain material reward or maintain their jobs. To achieve these selfish desires, most athletes, coaches and supporters engage in acts against the rules. and regulations of the game thereby stimulating violence in sports arena. The recent. societal attitude to sports portrays false value hence antithesis of the spirit of sportsmanship which wasfounded on respect for universal fundamental ethical principles of harmonious development of man, with a view to encouraging the establishment of a peaceful society thereby maintaining social health. This paper reviewed causes ofviolence; theoretical explanations of sports violence, and Social health implications of violence, possible solutions to sports violence and recommendations.